Republic of Mozambique : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper documents the main features of the current monetary policy regime in Mozambique, describe ongoing structural policy changes announced by the central bank, and analyze the main challenges facing the central bank in the process to modernize its monetary policy framework. Recognizing the signaling value of interest rates to anchor inflation expectations and help influence market interest rates, the paper usefully focuses on the needed reforms to enable the central bank to successfully replace monetary aggregates by interest rate as the main instrument of monetary policy. Deepening the understanding of the obstacles on the way to a smooth monetary transmission, further building the central bank inflation forecasting capacity, strengthening the coordination between fiscal and monetary policies, enhancing central bank communications and modernizing the legal framework to ensure central bank operational autonomy are essential to the success of the new monetary regime. Importantly, the presence of a committed and strong technical team and a reform-oriented management should greatly facilitate the implementation of these vital central bank reforms.